2013
DOI: 10.30638/eemj.2013.066
|View full text |Cite
|
Sign up to set email alerts
|

Driving Forces of Weee Management: A Pest Analysis of Romania

Abstract: Waste electrical and electronic equipment (WEEE, e-waste) represent the category of municipal waste with the fastest growth rate of the quantities generated particularly in developed countries. In Romania the WEEE management concerns have emerged recently and the amount of information and data available is limited and sometimes irrelevant. In this case, studying the forces that influence WEEE management system directly or indirectly is useful for both the national and international stakeholders. In this contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In order to make a realistic picture of the WEEE field in Romania, we have reviewed and analysed information from several sources. (Ciocoiu et al, 2009;Popescu, 2014;Rudăreanu, 2014), WEEE management system (Caluseru et al, 2010;Ciocoiu, 2012;Ciocoiu and Tartiu, 2012;Ciocoiu et al, 2010a;Ciocoiu et al, 2011b;Ciocoiu et al, 2013;Ghiban et al, 2012;Hîncu et al, 2012;Ivănuş and Băbiţă, 2009;Popescu et al, 2014;Tartiu, 2009;Torreta et al, 2013;Zlamparet et al, 2015), WEEE behaviour (Colesca et al, 2014) and WEEE recovery, recycling and environmental impact (Banacu et al, 2014;Ciocoiu et al, 2010b;Dăscălescu et al, 2012;Degeratu, 2012;Salanţă et al, 2013). A survey made in 2014 among Romanian universities and research institutes implied in waste research (Ciocoiu et al, 2014) showed that only 21.73% of respondents have had partial preoccupations in the WEEE field.…”
Section: Methodology Researchmentioning
confidence: 99%
“…In order to make a realistic picture of the WEEE field in Romania, we have reviewed and analysed information from several sources. (Ciocoiu et al, 2009;Popescu, 2014;Rudăreanu, 2014), WEEE management system (Caluseru et al, 2010;Ciocoiu, 2012;Ciocoiu and Tartiu, 2012;Ciocoiu et al, 2010a;Ciocoiu et al, 2011b;Ciocoiu et al, 2013;Ghiban et al, 2012;Hîncu et al, 2012;Ivănuş and Băbiţă, 2009;Popescu et al, 2014;Tartiu, 2009;Torreta et al, 2013;Zlamparet et al, 2015), WEEE behaviour (Colesca et al, 2014) and WEEE recovery, recycling and environmental impact (Banacu et al, 2014;Ciocoiu et al, 2010b;Dăscălescu et al, 2012;Degeratu, 2012;Salanţă et al, 2013). A survey made in 2014 among Romanian universities and research institutes implied in waste research (Ciocoiu et al, 2014) showed that only 21.73% of respondents have had partial preoccupations in the WEEE field.…”
Section: Methodology Researchmentioning
confidence: 99%
“…Additionally, the proposed framework is centered on empirical research with primary stakeholders to generate knowledge collectively, also considering the perspectives of incubated entrepreneurs and their daily-lived experiences; numerous academics called for in-depth qualitative studies incorporating these understandings [10,[59][60][61][62][63][64]. Previous virtual business incubator models were proposed by other researchers based essentially on case studies [27,28,37], literature review [33][34][35], questionnaires [30][31][32], website analysis, and semi-structured interviews [38].…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…A similar incubator model from Romania was proposed to enhance business, research, and academic opportunities focused on environmental and eco-innovation issues concerning electrical and electronic equipment waste recycling [32]. Although this model did not encompass 3D virtual spaces for its operation, it was organized in four dimensions: knowledge and training; local, national, and international events; innovation, knowledge, and technology transfer; and access to funds.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming to develop a virtual hub for eco-innovation in the field of electrical and electronic equipment (e-waste) recycling, Ciocoiu, Colesca, Pacesila, and Burcea [34] conducted a questionnaire in Romania and proposed a model based on the considerations and requirements of 43 experts from universities and research and development institutes. The virtual eco-innovation hub aims to promote business, academic, and research opportunities, and is organized in a model with four principal dimensions, namely knowledge and training, access to national and international events, innovation, knowledge, and technology transfer, and access to funds.…”
Section: Systematic Literature Review Based On Content Analysismentioning
confidence: 99%